2022
DOI: 10.3389/fonc.2022.857827
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Model to Predict the Prognosis of Patients With Retroperitoneal Liposarcoma: A Large International Population-Based Cohort Study

Abstract: BackgroundRetroperitoneal liposarcomas (RPLs), sarcoma of mesenchymal origin, are the most common soft tissue sarcomas (STS) of the retroperitoneum. Given the rarity of RPLs, the prognostic values of clinicopathological features in the patients remain unclear. The nomogram can provide a visual interface to aid in calculating the predicted probability that a patient will achieve a particular clinical endpoint and communication with patients.MethodsWe included a total of 1,392 RPLs patients diagnosed between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Among all 578 deaths in this study, 28.7% occurred due to causes other than RLMS, which accounts for a great part of total deaths. To avoid overestimating the risk of disease-related deaths, Fine & Gray's method was employed to develop our nomogram for predicting CSS of RLMS, which was also applied by Nazzani et al for surgically treated RPS [ 4 ] and Li et al for retroperitoneal liposarcoma [ 20 ]. After univariate analysis of CSS, five predictors with significance were identified, including grade, tumor size, tumor range, chemotherapy and surgery status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all 578 deaths in this study, 28.7% occurred due to causes other than RLMS, which accounts for a great part of total deaths. To avoid overestimating the risk of disease-related deaths, Fine & Gray's method was employed to develop our nomogram for predicting CSS of RLMS, which was also applied by Nazzani et al for surgically treated RPS [ 4 ] and Li et al for retroperitoneal liposarcoma [ 20 ]. After univariate analysis of CSS, five predictors with significance were identified, including grade, tumor size, tumor range, chemotherapy and surgery status.…”
Section: Discussionmentioning
confidence: 99%
“…However, nomograms to predict the probability of CSS for RLMS patients have not yet been constructed. Compared with traditional Cox analysis, the Fine & Gray method [ 19 ] is more accurate in survival analysis for considering the existence of competing events and has been applied in various tumors, including retroperitoneal liposarcoma [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they used the 5-cm threshold recommended by the AJCC staging system ( 6 , 38 ), whereas the thresholds (6.5-cm) we used were derived from an analysis based on a large database using X-tile software version 3.6.1 (Yale University School of Medicine, US) ( 22 ). Several studies have revealed that the AJCC T-classification system should be interpreted with caution because it still has limited predictive value for the prognosis of multiple tumors ( 50 , 51 ). Therefore, it was necessary to investigate the threshold of tumor size for each type of tumor in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…As the most common tissue type of retroperitoneal malignancy, retroperitoneal liposarcoma (RPLS) originates from the adipose tissue in the retroperitoneal space. Owing to the special anatomical structure and high malignancy, RPLS cases are often accompanied by insidious clinical symptoms and rapid progression [1][2][3]. Therefore, most RPLS neoplasms are huge and have a complex relationship with adjacent organs, making the operation difficult and often requiring combined organ resection.…”
Section: Introductionmentioning
confidence: 99%